Study of green spaces of Private Natural Heritage Reserves and their surroundings in the city of Manaus, Amazon (Revista Espinhaço, 2026)
The reduction of green areas in the city of Manaus has led to the increasing isolation of Private Natural Heritage Reserves (RPPNs), potentially impacting the biodiversity of these Conservation Units. We assessed the green areas of the RPPNs and their surroundings in 2019 and 2022. We quantified the green areas of the RPPNs, and classified maps were created for analysis. Seven RPPNs were included in the study, requiring the acquisition of the polygon for each area in shapefile format (.ssp) and processed in QGIS software. A buffer of 1000 and 2000 meters from a centroid was applied to obtain a wide analyzable area. The images obtained from Planet Labs for the years 2019 and 2022, making a mosaic to join the bands and generate a single image. The classification applied included supervised and unsupervised methods, using SAGA GIS software. The map created revealed significant reductions in green areas around the RPPNs. The use of supervised classification using the maximum likelihood method made it possible to distinguish and verify the changes in green areas in the RPPNs and their surroundings. Significant reductions in the green areas around the RPPNs in the urban area of Manaus stand out, made possible by analysis and classification using the maximum likelihood method.
Keywords: RPPN; Image classification; Urban expansion